Abnormal platelet activity in dogs and cats – impact and measurement. (9th January 2020) - Gant, P.; McBride, D.; Humm, K.
Abstract : Abnormal platelet activity can either lead to bleeding tendencies or inappropriate thrombus formation and can occur secondarily to a wide variety of disease processes, with a range of clinical consequences and severity. This article will discuss the pathophysiology of platelet function abnormalities and consider a logical diagnostic approach applicable to veterinary practice. Recent advances in platelet function testing will then be discussed, with regards to detection of platelet dysfunction and tailoring of pharmacological manipulation. Although many of these tests are still confined to research or academic institutions, techniques for indirectly assessing platelet function are starting to become more widely available. Although we still require further research to develop guidelines for the use of these tests in clinical decision‐making, the recent advances in this field are an exciting step forward in being able to detect and manage platelet dysfunction in both primary care and referral practice.